GUIDANCE AND COUNSELING SERVICES IN THE DIGITAL AGE: ENHANCING ADOLESCENTS’ SPIRITUAL AWARENESS THROUGH SOCIAL MEDIA - Trisna Cita Eka Novyani; Anwar Sutoyo; Muslikah (EDUCATIONE, 2025)
Adolescents are in a critical phase of personal and spiritual development, yet their increasing exposure to social media trends often creates challenges such as reduced self-awareness, weakened moral grounding, and decreased spiritual sensitivity. This research aims to explore the role of Guidance and Counseling (BK) services in enhancing adolescents’ spiritual awareness through the utilization of social media platforms. Employing a qualitative approach with the Systematic Literature Review (SLR) method, the study synthesizes findings from various peer-reviewed articles published between 2015–2024 that address the intersection of counseling, spiritual growth, and digital media. The results reveal that BK services conducted through social media enable counselors to deliver spiritual education, foster reflective group discussions, and provide personalized online counseling while simultaneously disseminating inspirational content. These practices have been shown to promote adolescents’ ability to manage stress, recognize the impact of online behavior, and internalize spiritual values. The findings also emphasize the significance of BK teachers adopting holistic and psychologically grounded approaches in addressing spiritual challenges in digital contexts. The study concludes that integrating BK services with social media can effectively strengthen spiritual awareness among adolescents when supported by appropriate supervision and structured program design. This research contributes practical insights for educational institutions in optimizing digital platforms for character and spiritual development. Future research should focus on testing specific BK models that integrate spirituality and digital literacy across diverse educational settings.